Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

STAT3 activation through IL-6/IL-11 in cancer-associated fibroblasts promotes colorectal tumour development and correlates with poor prognosis - Heichler, Christina; Scheibe, Kristina; Schmied, Anabel; Geppert, Carol-Immanuel; Schmid, Benjamin; Wirtz, Stefan; Thoma, Oana Maria; Kramer, Viktoria; Waldner, Maximilian; Büttner, Christian; Farin, Henner; Pešić, Marina; et al. (Gut, 2019)
Objective: Cancer-associated fibroblasts (CAFs) influence the tumour microenvironment and tumour growth. However, the role of CAFs in colorectal cancer (CRC) development is incompletely understood. Design: We quantified phosphorylation of STAT3 (pSTAT3) expression in CAFs of human colon cancer tissue using a tissue microarray (TMA) of 375 patients, immunofluorescence staining and digital pathology. To investigate the functional role of CAFs in CRC, we took advantage of two murine models of colorectal neoplasia and advanced imaging technologies. In loss-of-function and gain-of-function experiments, using genetically modified mice with collagen type VI (COLVI)-specific signal transducer and activator of transcription 3 (STAT3) targeting, we evaluated STAT3 signalling in fibroblasts during colorectal tumour development. We performed a comparative gene expression profiling by whole genome RNA-sequencing of fibroblast subpopulations (COLVI+ vs COLVI-) on STAT3 activation (IL-6 vs IL-11). Results: The analysis of pSTAT3 expression in CAFs of human TMAs revealed a negative correlation of increased stromal pSTAT3 expression with the survival of colon cancer patients. In the loss-of-function and gain-of-function approach, we found a critical role of STAT3 activation in fibroblasts in driving colorectal tumourigenesis in vivo. With different imaging technologies, we detected an expansion of activated fibroblasts in colorectal neoplasias. Comparative gene expression profiling of fibroblast subpopulations on STAT3 activation revealed the regulation of transcriptional patterns associated with angiogenesis. Finally, the blockade of proangiogenic signalling significantly reduced colorectal tumour growth in mice with constitutive STAT3 activation in COLVI+ fibroblasts. Conclusion: Altogether our work demonstrates a critical role of STAT3 activation in CAFs in CRC development.
CRIS-Team Scopus Importer:2019-11-19
Keywords: colorectal cancer

Targeting STAT3 Signaling in COL1+ Fibroblasts Controls Colitis-Associated Cancer in Mice - Heichler, Christina; Schmied, Anabel; Enderle, Karin; Scheibe, Kristina; Murawska, Marta; Schmid, Benjamin; Waldner, Maximilian; Neurath, Markus; Neufert, Clemens (Cancers, 2022)
Colorectal cancer (CRC) is a common disease and has limited treatment options. The importance of cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME) in CRC has been increasingly recognized. However, the role of CAF subsets in CRC is hardly understood and opposing functions of type I (COL1+) vs. type VI (COL6+) collagen-expressing subsets were reported before with respect to NFκB-related signaling. Here, we have focused on COL1+ fibroblasts, which represent a frequent CAF population in CRC and studied their role upon STAT3 activation in vivo. Using a dual strategy with a conditional gain-of-function and a conditional loss-of-function approach in an in vivo model of colitis-associated cancer, tumor development was evaluated by different readouts, including advanced imaging methodologies, e.g., light sheet microscopy and CT-scan. Our data demonstrate that the inhibition of STAT3 activation in COL1+ fibroblasts reduces tumor burden, whereas the constitutive activation of STAT3 promotes the development of inflammation-driven CRC. In addition, our work characterizes the co-expression and distribution of type I and type VI collagen by CAFs in inflammation-associated colorectal cancer using reporter mice. This work indicates a critical contribution of STAT3 signaling in COL1+ CAFs, suggesting that the blockade of STAT3 activation in type I collagen-expressing fibroblasts could serve as promising therapeutic targets in colitis-associated CRC. In combination with previous work by others and us, our current findings highlight the context-dependent roles of COL1+ CAFs and COL6+ CAFs that might be variable according to the specific pathway activated.
CRIS-Team Scopus Importer:2022-03-25
Keywords: AOM/DSS model; Collagen; Colorectal cancer; Fibroblast; Inflammation; Tumorigenesis